Recreational tools for strengthening gross motor skills in the lower limbs (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2019)
Gross motor skills refer to all actions that involve large movements and, therefore, large muscle groups. This type of motor skill is vital for the child's overall development, involving movements of the arms, legs, back, and abdomen, enabling them to explore the world around them. Proper stimulation will develop the ability to climb stairs, crawl, hold up the head, roll over, and maintain balance, among other skills. However, it has been shown that during pregnancy, some women overstimulate their children, that is, they provide them with stimuli that exceed what they can tolerate in relation to their age or quantity, such that they cannot process them properly.